Ultrasonographic features of malignant catarrhal fever induced corneal oedema in cattle - ATHAR, HAKIM; PARRAH, JALAL UD DIN; KASHOO, ZAHID AMIN; WANI, SHAKIL AHMAD; MALIK, HAMIDULLAH; MOULVI, BASHIR AHMAD; MAKHDOOMI, DIL MOHAMMED; DAR, MEHRAJ U DIN (The Indian Journal of Animal Sciences, 2021)
The study was aimed to record the ocular ultrasonographic changes in the confirmed clinical cases of MCF. The cases were confirmed using hemi-nested polymerase chain reaction assay. Ocular ultrasonography was performed using a 10–18 MHz linear transducer (My Lab 40 Vet). Clinical signs observed were corneal oedema, lacrimation, photophobia, corneal oedema and hyperaemia of conjunctiva. In two animals, mild corneal oedema was observed while in four animals each, moderate and severe corneal oedema was recorded. In all the animals, corneal oedema initially appeared at the limbus with subsequent involvement of the entire cornea with varying degree of severity. Hemi-nested polymerase chain reaction was used for confirming the diagnosis. Ocular ultrasonographic examination revealed significant increase in the thickness of the cornea, iris and ciliary body. Anterior uveitis, characterized by thickened iris, exhibiting crust and trough formation covering the major part of the anterior surface of the lens was recorded in nine animals. There was no recovery in any of the case and the animals died within one month of the diagnosis of the MCF. Significant ultrasonographic changes were evident in eyes of animals affected with the malignant catarrhal fever. Ultrasonography may therefore be used for monitoring the ocular changes especially in the anterior segment of the opaque eyes.